Enhancing Vocational Students’ Critical Thinking Through Creative Short Story Writing Training - Jumadi Jumadi; Rustam Effendi; Sainul Hermawan; Muhammad Rafiek; Ahsani Taqwiem; Lita Luthfiyanti; Faradina Faradina (Universitas Lambung Mangkurat, 2026)
This community service activity aims to strengthen the critical thinking skills of vocational high school students through creative short story writing workshops. The main challenges faced by students include low levels of critical thinking and creative writing skills, particularly in identifying problems, formulating conflicts, and structuring a logical plot. This community service employed the Asset-Based Community Development (ABCD) approach, which emphasizes leveraging the potential and assets possessed by students and the school. The implementation method included the Discovery, Dream, Design, Define, and Destiny phases, carried out through training, mentoring, discussions, and a structured short story writing activity. Evaluation was conducted using a pretest and posttest design involving 40 students. The pretest results indicated that students’ initial abilities fell into the moderate category, with scores predominantly ranging from 60 to 75. Following the training, the posttest results showed a significant improvement, with the majority of students achieving scores in the 80–90 range. These research results suggest that creative short story writing training is effective in enhancing students’ critical thinking skills, writing abilities, and self-confidence in communicating ideas in writing. Thus, creative short story writing training based on the ABCD approach can serve as a relevant alternative learning strategy for strengthening literacy and developing 21st-century competencies.